Comparison of added resistance methods using digital twin and full-scale data. (1st June 2021) - Taskar, Bhushan; Andersen, Poul
Abstract: In this paper, full-scale data for two ships have been used for the comparison of five different added resistance methods. The effect of using separate wave spectra for wind waves and swell on performance prediction has been explored. The importance of the peak enhancement factor(γ) in the JONSWAP spectrum for added resistance computation has been studied. Simulation model including calm water resistance, added resistance and wind resistance has been used. Ships have been simulated in the same weather conditions and propeller speed as in the case of full-scale ships using different methods for added resistance. The performance of these methods has been quantified by comparing speed and power predictions with the full-scale data. The paper also discusses the challenges involved in using full-scale data for such a comparison because of difficulty in isolating the effect of added resistance in full-scale data. It was observed that three out of five methods were able to predict added resistance even in high waveheights. Even though these methods showed significantly different RAOs, its effect on speed and power prediction was minor. Simulation results were not sensitive to the choice of peak enhancement factor(γ) in the JONSWAP spectrum. There was minor improvement in results by using separate wave spectra for wind waves and swell instead of single wave spectrum for combined wind waves and swell. Highlights: Digital twin has been used for performance prediction in different weather conditions. Speed & power predictions using digital twin have been compared with full-scale data. Challenges in isolating added resistance effects in the data have been discussed. The effect of using separate spectra for wind waves and swell has been studied. The importance of spectral peakedness factor has been investigated.